1983
DOI: 10.1016/0035-9203(83)90022-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of diphetarsone in the treatment of amoebiasis, non-pathogenic amoebiasis and trichuriasis

Abstract: Eighty-nine patients infected with Entamoeba histolytica, non-pathogenic amoebae or Trichuris trichiura were studied prospectively to determine the safety and efficacy of diphetarsone therapy. An additional 75 patients were studied retrospectively to assess further the efficacy of diphetarsone in the treatment of E. histolytica cyst passers. Side effects were noted in 9% and included gastrointestinal upset, lightheadedness and headache. Transient liver function abnormalities were recorded in 5.6%. diphetarsone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Agents used for the treatment of dientamoebiasis have been associated with several side‐effects. Diphetarsone has been associated with transient liver function abnormalities [15], while tetracycline is contraindicated in children because of its deleterious effects on dental development [1]. However, a recent study reported no side‐effects following the use of paromomycin in paediatric patients [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agents used for the treatment of dientamoebiasis have been associated with several side‐effects. Diphetarsone has been associated with transient liver function abnormalities [15], while tetracycline is contraindicated in children because of its deleterious effects on dental development [1]. However, a recent study reported no side‐effects following the use of paromomycin in paediatric patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of compounds has been used, with varying efficacies, in the treatment of dientamoebiasis, including metronidazole [11], iodoquinol [12], tetracycline [13], erythromycin [14], diphetarsone [15], paromomycin [16] and secnidazole [2]. Chan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its efficacy in eradicating D. fragilis, carbarsone is no longer available for human use. The newer arsenic compound diphetarsone showed 100% efficacy (188). Despite being a widely used first-line treatment for intestinal amoebiasis, side effects associated with the use of arsenicals, such as encephalopathy, polyneuritis, visual disturbances, and dermatitis, led to the drug being removed from clinical practice and not licensed for human use (188).…”
Section: Arsenic-based Compoundsmentioning
confidence: 99%
“…Transient liver function abnormalities were observed in several patients treated with diphetarsone (70). Tetracycline has limited usefulness in children because of its well-established deleterious effect on dental development.…”
Section: Transmissionmentioning
confidence: 99%